2018
DOI: 10.1016/j.ajo.2017.12.018
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Longitudinal Study to Investigate Corneal Hysteresis as a Risk Factor for Predicting Development of Glaucoma

Abstract: Baseline lower CH measurements were significantly associated with increased risk of developing glaucomatous visual field defects over time. The prospective longitudinal design of this study supports a role of CH as a risk factor for developing glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 24 publications
2
59
0
1
Order By: Relevance
“…[41][42][43][44][45] The association between CH and LCCI provides a plausible explanation for the association of CH with glaucoma progression. [41][42][43][44][45] In eyes with smaller hysteresis, pressure would not be dissipated too much. Thus, a higher proportion of IOP-derived energy would be used in elastic changes resulting in greater LC deformation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43][44][45] The association between CH and LCCI provides a plausible explanation for the association of CH with glaucoma progression. [41][42][43][44][45] In eyes with smaller hysteresis, pressure would not be dissipated too much. Thus, a higher proportion of IOP-derived energy would be used in elastic changes resulting in greater LC deformation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A lower CH is associated with the risk of developing glaucoma (Susanna et al. ), with glaucoma progression (Medeiros et al. ) as well as the severity of the disease (Pillunat et al.…”
Section: Introductionmentioning
confidence: 99%
“…This prompted our decision to separately evaluate male and female groups, as well as older and younger, groups. Other studies have already demonstrated that low CH is associated with glaucoma progression 3,4 . Here, we evaluated the relationship between systemic antioxidative status and CH; to the best of our knowledge, this is the first study to do so.…”
Section: Discussionmentioning
confidence: 86%
“…Even when IOP is stable, optic nerve head damage can vary between individuals due to differing susceptibility to glaucomatous damage 2 . Some researchers have found that glaucoma progression is related to specific material properties of the cornea, such as the strength of corneal viscoelastic damping, known as corneal hysteresis (CH) 3,4 . CH can be measured by temporarily inducing a concave deformation in the cornea with a pulse of air.…”
mentioning
confidence: 99%